Study of Stirling Engine Efficiency Coefficient under Conditions Being Close to Real Ones - R. M. Abramian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An absolute internal efficiency coefficient of the Stirling engine has been obtained without regenerator and with regenerator under conditions when van der Waals gas serves as a working medium. The paper reveals that while taking into account own volume of molecules thermal efficiency coefficient of the Stirling engine depends on mole number of the working medium  and it is slightly increasing  in comparison with the case of an ideal gas. The paper gives consideration to heat losses while the Stirling machine operates with heat regeneration. Dependence of regeneration rate on time of heat transfer has been obtained in the paper.